Revitalisasi Pewarna Alami Dalam Industri Tenun Ikat Sebagai Penggerak Ekonomi Rumah Tangga: (Studi Kasus Di Kelurahan Lambanapu Dan Desa Kambatatana) - Frederika Uru Ende; Magdalena Kahi Timba; Yulius Hou Duka; R.L.K.R Nugrohowardhani; Yuvensius Ramompas; Martini Ndamunamu (Jurnal Neo Societal, 2025)
This study aimed to understand the forms of natural dye revitalization in the dyeing process of threads used for producing ikat textiles and its impact on the household economy of ikat artisans. Various studies related to revitalization are employed as the analytical framework for this research. A qualitative research method with a case study strategy was used. Data were collected through interviews, observations, and documentation, and subsequently analyzed using thematic analysis. The study was conducted in two locations, namely Lambanapu Village and Kambatatana Village in East Sumba Regency. The findings reveal that the revitalization of natural dyes in the two research locations can be categorized into three forms: new tools, new natural dye materials, and new extraction techniques. From a household economic perspective, the production of ikat textiles has become a primary source of income, used to meet basic needs, fund children's education, and support traditional ceremonies. This study concludes that the revitalization of natural dyes not only strengthens cultural heritage but also enhances economic and environmental sustainability.